(untitled) (Research, Society and Development, 2022)
Introduction: Increasing worldwide overweight rates in children are concerning and reinforce the risk of several chronic diseases in adulthood. An overview of the status regarding childhood excess weight in Brazil is essential to understand, formulate and improve actions to face this condition and accomplish health and quality of life to Brazilian children and adolescents. Objective: Systematically describe childhood overweight and obesity rates and its associated factors. Methods: Systematic review of studies published between 2015 and 2019, based on search in electronic databases PubMed, Scielo, MEDLINE, LILACS, ADOLEC and Science Direct. The STROBE scale was used to evaluate the quality of the studies included. Results: Out of 1334 studies screened, 23 studies were included in this review. The prevalence of overweight, overweight and obesity ranged from 0.9% to 35.4%, being higher in the country’s Southern region and with slight variations in terms of sex and age. Conclusion: Due to the methodological differences present in the selected studies, it was found variability between the prevalence rates of excess weight in children in Brazil. This review reflects the necessity of facing this condition in Brazilian children and adolescents.